2010
DOI: 10.1128/aem.02425-09
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of Survival and Electricity Production in an Engineered Bacterium by Light-Driven Proton Pumping

Abstract: Microorganisms can use complex photosystems or light-dependent proton pumps to generate membrane potential and/or reduce electron carriers to support growth. The discovery that proteorhodopsin is a light-dependent proton pump that can be expressed readily in recombinant bacteria enables development of new strategies to probe microbial physiology and to engineer microbes with new light-driven properties. Here, we describe functional expression of proteorhodopsin and light-induced changes in membrane potential i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
67
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 84 publications
(74 citation statements)
references
References 44 publications
7
67
0
Order By: Relevance
“…Subsequent studies on aquatic PR-containing bacteria have confirmed this finding (146). In a heterologous expression system, S. oneidensis MR-1 produced 4.0 ϫ 10 4 PR molecules per cell while growing anaerobically in minimal medium (15). In another heterologous expression system, Martinez et al (127) found that starved E. coli harboring recombinant PR retrieved 2.2 ϫ 10 5 molecules of ATP from 5 min of illumination, which was compared to 9 ϫ 10 5 molecules of ATP from heterotrophic utilization of succinate under similar conditions.…”
Section: Toward Quantification Of Marine Photoheterotrophymentioning
confidence: 50%
See 1 more Smart Citation
“…Subsequent studies on aquatic PR-containing bacteria have confirmed this finding (146). In a heterologous expression system, S. oneidensis MR-1 produced 4.0 ϫ 10 4 PR molecules per cell while growing anaerobically in minimal medium (15). In another heterologous expression system, Martinez et al (127) found that starved E. coli harboring recombinant PR retrieved 2.2 ϫ 10 5 molecules of ATP from 5 min of illumination, which was compared to 9 ϫ 10 5 molecules of ATP from heterotrophic utilization of succinate under similar conditions.…”
Section: Toward Quantification Of Marine Photoheterotrophymentioning
confidence: 50%
“…Johnson et al investigated the benefit of PR proton pumping for physiological functions in another heterotrophic Gammaproteobacteria species, Shewanella oneidensis MR-1, in part also to explore potential practical aspects of metabolic engineering (15). The PR gene from a SAR86 clade bacterium expressed from a broad-host-range vector in S. oneidensis resulted in an estimated 40,000 PR molecules per cell, and light exposure of starving cells caused similar levels of energized cells as amendment of the medium with lactate as an organic matter source under anaerobic conditions.…”
Section: Clues To the Mechanisms Of Proteorhodopsin Photophysiology Fmentioning
confidence: 99%
“…PRs have also been heterologously expressed in non-photosynthetic hosts (5,(21)(22)(23)(24)(25). For example, the introduction of a PR in Shewanella oneidensis increased the pmf, which resulted in increases in electrical current generation, lactate uptake, and survival under starvation conditions (23,24).…”
Section: Introductionmentioning
confidence: 99%
“…For example, the introduction of a PR in Shewanella oneidensis increased the pmf, which resulted in increases in electrical current generation, lactate uptake, and survival under starvation conditions (23,24). In Escherichia coli, the pmf generated by a PR resulted in ATP synthesis (22), was able to drive the flagellar motor (21), and could be used to significantly increase the production of hydrogen by a co-introduced hydrogenase (25,26).…”
Section: Introductionmentioning
confidence: 99%
“…Characterization studies of proton motive force (PMF) in MR-1 have not definitively determined whether the source of anaerobic proton pumping or translocation is electron transport, ATP synthase, or metabolite transport (13,19). Myers et al demonstrated that anaerobic MR-1 cells starved of electron acceptor generate PMF in response to fumarate addition (19).…”
mentioning
confidence: 99%